A Research on the Fair Play Behaviors of Students Participating in School Sports (The Case of Düzce Province) - GORUN, Levent (Asian Journal of Education and Training, 2020)
The aim of this study is to examine the fair play behaviours of students who attend school sports. The universe of the research is 2631 participants studying in the Central District of Düzce in the 2019-2020 Academic Year and competing in volleyball, basketball, football and individual branches in secondary and high schools, while the sample is 397 participants on a voluntary basis. In the research, the personal information form created by the researchers and "Fair Play Scale" (FP) developed by Efe (2006) were used as a measurement tool. The scale consists of four subscales: “pre-match fair play”, “during-match fair play”, “after-match fair play” and “general fair play in a match”. While there is a statistically significant difference in all subscales according to the categories, when compared to the sports age, there is a statistical difference only in the fair play behaviours during the match. Also, when fair play behaviours are compared according to the branch, a statistically significant difference is observed according to the subscales of pre-match, during the match and general fair play behaviours. As a result, it can be said that fair play behaviours, which vary according to the branch, sports age and categories, can be spread to social life after school with trainings suitable for the development periods and the requirements of the sports branches.